Genetic and environmental factors in the spread of some genetic diseases in polluted areas of southern Iraq / Review Article - Shaima Dawood Salman; Zahraa Radhi Shadhan; Yasamin Abdul Amer Kadhum; Estabraq Mohammed Ati; Reyam Naji Ajmi (Peerian Journals Publishing, 2025)
The southern governorates of Iraq, particularly Basra, Nasiriyah, and Muthanna, are witnessing an alarming increase in the rates of genetic diseases. This is the result of a complex interaction between genetic factors and long-term exposure to environmental pollutants such as heavy metals (lead, mercury, cadmium) and perfluorooctanoic hydrocarbons (PAHs). Recent studies have shown that this interaction is not limited to a direct causal relationship, but rather includes disturbances in DNA repair mechanisms and alterations in gene expression resulting from environmental stress. Genetic factors, such as high rates of consanguineous marriages (reaching more than 45% in some areas of Basra), indicate a significant role in the spread of recessive diseases such as sickle cell anemia and thalassemia, especially in light of the weakness of premarital genetic screening programs. It was found that less than 20% of couples in these governorates underwent genetic testing, leaving large numbers of carriers of genetic mutations unidentified. On the environmental level, the concentration of heavy metals and industrial activity associated with oil extraction contribute to DNA damage and the accumulation of genetic mutations through what is known as oxidative stress
Keywords: Environmental Pollution; Genetic Diseases; Epigenetic Modifications